Dynamics in stochastic evolutionary models - David Knudsen Levine; Salvatore Modica (Theoretical Economics, 2016)
We characterize transitions between stochastically stable states and relative ergodic probabilities in the theory of the evolution of conventions. We give an application to the fall of hegemonies in the evolutionary theory of institutions and conflict and illustrate the theory with the fall of the Qing Dynasty and rise of Communism in China.
Keywords: C73; 330; Evolution; conventions; markov chains; state power